2016
DOI: 10.1152/ajpheart.00807.2015
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol-responsive microRNAs, miR-199a-3p and -214 protect cardiomyocytes from simulated ischemia-reperfusion injury

Abstract: The nonselective β-adrenergic receptor antagonist (β-blocker) carvedilol has been shown to protect against myocardial injury, but the detailed underlying mechanisms are unclear. We recently reported that carvedilol stimulates the processing of microRNA (miR)-199a-3p and miR-214 in the heart via β-arrestin1-biased β1-adrenergic receptor (β1AR) cardioprotective signaling. Here, we investigate whether these β-arrestin1/β1AR-responsive miRs mediate the beneficial effects of carvedilol against simulated ischemia/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 58 publications
(93 reference statements)
5
44
0
Order By: Relevance
“…185190 miR-199a-3p and miR-214 are activated by carvedilol in cardiomyocytes subjected to ischemia/reperfusion and promote cardiomyocyte survival by activating p-Akt survival signaling, inducing the expression SRY (sex determining region Y)-box 2 (Sox2), a transcription factor that promotes pluripotency and also by repressing the apoptosis-associated genes ddit4 (DNA damage-inducible transcript 4) and ing4 (inhibitor of growth family member 4). 191 miR-190 upregulation by carvedilol occurs via the β 1 AR and is independent of β 2 AR and α 1 AR activation. It also requires specific activated conformations of the receptor, β 1 AR’s phosphorylation by GRKs 5 or 6 and the recruitment of β-arrestin1 to the carvedilol bound-receptor complex.…”
Section: β-Arrestin-biased Agonistsmentioning
confidence: 89%
“…185190 miR-199a-3p and miR-214 are activated by carvedilol in cardiomyocytes subjected to ischemia/reperfusion and promote cardiomyocyte survival by activating p-Akt survival signaling, inducing the expression SRY (sex determining region Y)-box 2 (Sox2), a transcription factor that promotes pluripotency and also by repressing the apoptosis-associated genes ddit4 (DNA damage-inducible transcript 4) and ing4 (inhibitor of growth family member 4). 191 miR-190 upregulation by carvedilol occurs via the β 1 AR and is independent of β 2 AR and α 1 AR activation. It also requires specific activated conformations of the receptor, β 1 AR’s phosphorylation by GRKs 5 or 6 and the recruitment of β-arrestin1 to the carvedilol bound-receptor complex.…”
Section: β-Arrestin-biased Agonistsmentioning
confidence: 89%
“…The miR‐214‐deficient mice were susceptible to lethal ischemia‐reperfusion (I/R)‐induced myocardial oxidative injury with increased Ca 2+ overload and pro–apoptotic Bcl2l11, 46 while overexpression of miR‐214 protected the heart from I/R injury through suppression of PTEN, Bcl2l11, 47 ddit4 or ing4 48 . In contrast, the inhibition of miR‐199 or miR‐214 suppressed cellular proliferation in primary pancreatic stellate cells, 49 suggesting a potential therapeutic target in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, since this disease is associated with multiple factors, new regulatory factors that are of significant importance need to be identified. Studies in recent years have found that miRNAs, as a post-transcriptional regulatory factor, can simultaneously target multiple mRNAs involved in different signaling pathways, and thereby regulate gene expression either at the transcriptional or at the post-transcriptional level [28]. Thus, various intracellular cytokines and signaling pathways work in synergy under miRNA regulation [29].…”
Section: Discussionmentioning
confidence: 99%